LITERATURE STUDY OF THE BENEFITS OF NONI FRUIT (Morinda citrifolia) AS AN ANTIMICROBIAL - Suhendriyo; Kirwanto, Agus; Indarto; Maulinda, Yuni; Yulianto, Susilo (Jurnal Jamu Kusuma, 2024)
Herbal plants that can be used as antimicrobials are noni fruit (Morinda citrifolia). The fruit contains saponins, flavonoids, essential oils, and alkaloids, which have potential as antimicrobials, in noni fruit. The type of research used is a literature study review. The study literature review is a summary obtained from a reading source such as books, scientific journals, and other media publications relating to the discussion of research in order to answer questions or existing problems. A literature search was performed on electronic sources such as Google Scholar, PubMed, and Garuda Portal which have met the inclusion and exclusion criteria. Based on search results by entering the word the key obtained as many as 906 articles and only 3 articles that meet the requirements. The results of the study can be concluded that noni fruit (Morinda citrifolia) can be used as antimicrobial and phytochemical compounds in Noni fruit which has the potential as an antimicrobial are flavonoids, saponins, essential oils, terpenoids, alkaloids, scopoletin, ascorbic acid, beta carotene, l-arginine, and proxeronine.